Perception and views about individualising antibiotic duration for respiratory tract infections when patients feel better: a qualitative study with primary care professionals - Josep M Cots; Ana Moragas; Carl Llor; Lars Bjerrum; Paula Uguet; Albert Boada (BMJ Open)
Background Evidence shows a high rate of unnecessary antibiotic prescriptions for respiratory tract infections (RTIs) in primary care. There is increasing evidence showing that shorter courses for RTIs are safe and help in reducing antimicrobial resistance (AMR). Stopping antibiotics earlier, as soon as patients feel better, rather than completing antibiotic courses, may help reduce unnecessary exposure to antibiotics and AMR.Objectives The aim of this study was to explore the perceptions and views of primary care healthcare professionals about customising antibiotic duration for RTIs by asking patients to stop the antibiotic course when they feel better.Design Qualitative research.Setting and participants A total of 21 qualitative interviews with primary care professionals (experts and non-experts in AMR) were conducted from June to September 2023. Data were audiorecorded, transcribed and analysed thematically.Results Overall, experts seemed more amenable to tailoring the antibiotic duration for RTIs when patients feel better. They also found the dogma of ‘completing the course’ to be obsolete, as evidence is changing and reducing the duration might lead to less AMR, but claimed that evidence that this strategy is as beneficial and safe as fixed courses was unambiguous. Non-experts, however, believed the dogma of completing the course. Clinicians expressed mixed views on what feeling better might mean, supporting a shared decision-making approach when appropriate. Participants claimed good communication to professionals and patients, but were sceptical about the risk of medicalisation when asking patients to contact clinicians again for a check-up visit.Conclusions Clinicians reported positive and negative views about individualising antibiotic courses for RTIs, but, in general, experts supported a customised antibiotic duration as soon as patients feel better. The information provided by this qualitative study will allow improving the performance of a large randomised clinical trial aimed at evaluating if this strategy is safe and beneficial.